Graphite polar plate, electrolytic phosphating process and application of graphite polar plate

The micro particles released through the graphite plate are evenly dispersed during the electrolytic phosphating process and adsorbed on the film layer, solving the problem of insufficient lubrication performance of the traditional electrolytic phosphating film layer and achieving better lubrication performance and cost-effectiveness.

CN119265670AActive Publication Date: 2025-01-07DONGGUAN YINGXING METAL SURFACE TREATMENT MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411437506.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-07
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

During the traditional electrolytic phosphating process, the lubricating performance of the phosphated film layer is insufficient, which limits its application in the fields of high-strength fasteners and moving mechanical components, and the improvement method is costly and the process is complex.

Method used

Graphite electrode plates are used to release graphite microparticles through their surfaces, so that the microparticles are evenly dispersed in the electrolyte and adsorbed on the phosphated film layer, reducing the friction coefficient and pulling force, and improving the lubricating performance of the film layer.

Benefits of technology

It significantly improves the lubricating performance of the phosphated film layer, reduces the cost and life of the drawing mold, and is lower than that of traditional precious metal anode plates, which has better cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265670A_ABST
    Figure CN119265670A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrolytic phosphating, in particular to a graphite polar plate, an electrolytic phosphating process and application of the graphite polar plate. The graphite polar plate comprises the following raw materials in percentage by weight: 10-20% of a binder, 1-5% of a conductive agent, 5-10% of carbon fibers and the balance of graphite powder, the particle size of the graphite powder is 32-100 [mu] m; the binder comprises one or more of phenolic resin, epoxy resin, furan resin or polytetrafluoroethylene resin; the conductive agent comprises one or more of graphene, carbon black or carbon nanotubes. When the graphite polar plate is applied to a phosphating process, the surface of the graphite polar plate can release graphite microparticles, the graphite microparticles are uniformly dispersed in an electrolyte, and the graphite microparticles adsorbed on a phosphating film layer can remarkably improve the lubricating performance of the film layer, reduce the friction coefficient and reduce the drawing force; therefore, the service performance and the service life of the drawing die are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrolytic phosphating, in particular to a graphite pole plate, an electrolytic phosphating process and applications thereof. Background Art

[0002] Electrolytic phosphating is a technology widely used in metal surface treatment. It can form a dense phosphate film on the metal surface. This phosphate film can effectively improve the metal's corrosion resistance and subsequent cold plastic processing performance. However, in the traditional electrolytic phosphating process, the lubrication performance of the phosphate film is often insufficient, which limits its use in certain specific application areas, such as high-strength fasteners, moving machinery parts, etc. In order to improve the lubricity of the phosphate film, researchers have tried a variety of methods, including improving the phosphating solution formula, optimizing the electrolytic process parameters, and adding back-end lubrication workers, but these methods often have problems such as high cost and complex process.

[0003] To this end, the present application provides a graphite electrode, an electrolytic phosphating process and applications thereof. Summary of the Invention

[0004] In response to the problems of high cost and complex process in the current phosphating improvement methods, the present application provides a graphite electrode, an electrolytic phosphating process and its application. When the graphite electrode described in the present application is used in the phosphating process, the surface of the graphite electrode can release graphite particles, and the graphite particles are evenly dispersed in the electrolyte. The graphite particles adsorbed on the phosphating film layer can significantly improve the lubrication performance of the film layer, reduce the friction coefficient, and reduce the drawing force, thereby improving the performance and life of the drawing die.

[0005] The technical solution adopted by this application to solve its technical problems is:

[0006] In a first aspect, the present application provides a graphite plate comprising the following raw materials by weight percentage:

[0007] Binder 10-20%, conductive agent 1-5%, carbon fiber 5-10%, and the balance is graphite powder;

[0008] The particle size of the graphite powder is 32-100 μm;

[0009] The binder includes one or more of phenolic resin, epoxy resin, furan resin or polytetrafluoroethylene resin;

[0010] The conductive agent includes one or more of graphene, carbon black or carbon nanotubes;

[0011] The carbon fibers include one or both of polyacrylonitrile-based carbon fibers and pitch-based carbon fibers.

[0012] In some specific embodiments, the method for preparing a graphite plate comprises the following steps:

[0013] S101. The graphite powder and binder are fed in the proportion of the raw materials for the graphite plate, heated, stirred and mixed to form a mixture;

[0014] S102. The conductive agent and carbon fiber are added to the mixture, and heating and stirring are continued to obtain a mixed raw material;

[0015] S103. The mixed raw materials are placed in a mold and pressed to obtain a molded blank;

[0016] S104. The formed blank is removed from the mold and cured;

[0017] S105. After curing, slowly cool to room temperature to obtain a plate blank;

[0018] S106. Perform sandblasting on the surface of the electrode plate blank to obtain a graphite electrode plate.

[0019] In some specific embodiments, in step S106, the sandblasting surface treatment comprises the following: the abrasive is aluminum oxide, the abrasive particle size is 120-180 mesh, the sandblasting pressure is 0.4-0.6 MPa, and the sandblasting time is 10-15 min.

[0020] In some specific embodiments, when the graphite plate is electrolytically phosphating, the surface of the graphite plate can release graphite particles, and the graphite particles are uniformly dispersed in the electrolyte.

[0021] In a second aspect, the present application provides an electrolytic phosphating process, using the graphite plate provided in the first aspect as an anode to perform electrolytic phosphating.

[0022] In some specific embodiments, the electrolytic phosphating process comprises the following steps:

[0023] S301. The graphite plate is installed in the electrolytic phosphating tank as an anode, connected to the positive electrode of the electrolytic power supply;

[0024] S302. The electrolytic phosphating solution is injected into the electrolytic phosphating tank, heated, and stirred;

[0025] S303. The raw material coil wire is sequentially connected to the straightening machine, abrasive belt machine, conductive pressure wheel, washing tank, electrolytic phosphating tank, post-wash tank, inverted take-up machine;

[0026] S304. Set the current density and wire speed, turn on the electrolytic phosphating power supply and inverted wire take-up, and perform electrolytic phosphating treatment on the raw wire.

[0027] In some specific embodiments, in step S302, the heating temperature is 40-60°C, and the stirring speed is maintained at 100-200 r / min.

[0028] In some specific embodiments, in step S304, the current density is 5-25A / dm 2 , the routing speed is maintained at 0.61.6m / s.

[0029] In some specific embodiments, each liter of electrolytic phosphating solution includes the following raw materials:

[0030] Phosphoric acid 130-150g, zinc oxide 75-90g, nitrate 80-120g, succinic acid 3-5g, citric acid 3-5g, polyphosphate 3-5g, polycarboxylate 3-5g, dodecylphenol polyoxyethylene ether 0.3-0.5g.

[0031] In a third aspect, the present application provides an application of an electrolytic phosphating process, applying the electrolytic phosphating process provided in the second aspect to the surface treatment of raw wire.

[0032] The beneficial effects of this application are:

[0033] (1) The graphite plate described in the present application has a surface that is easy to release microparticle structures. During the electrolytic phosphating process, the microparticles on the surface of the graphite plate can gradually fall off and disperse into the electrolyte. The graphite plate is low in cost and its price is significantly lower than the iridium, ruthenium and other precious metal anode plates commonly used in the current electrolytic phosphating process, and has good cost-effectiveness.

[0034] (2) In the electrolytic phosphating process described in the present application, during the electrolytic phosphating process, the microparticles released from the surface of the graphite plate can be evenly dispersed in the electrolyte and eventually adsorbed on the phosphating film layer of the metal wire; the graphite microparticles adsorbed on the phosphating film layer can significantly improve the lubrication performance of the film layer, reduce the friction coefficient, and reduce the drawing force, thereby improving the performance and life of the drawing die, and having good cost-effectiveness.

[0035] (3) The electrolytic phosphating process described in this application improves the lubrication performance of the phosphating film layer, reduces the use of saponification liquid and drawing powder at the back end of phosphating, and has good cost-effectiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The present invention will be further described below with reference to the accompanying drawings and examples.

[0037] Figure 1 The test results of the graphite plates for this application;

[0038] Figure 2 Electrolytic phosphating solution was prepared for Example 3 and Comparative Examples 1, 2, and 3;

[0039] Figure 3 This is a metallographic photograph of the electrolytic phosphating film obtained in Example 3;

[0040] Figure 4 The metallographic photograph of the electrolytic phosphating film obtained in Comparative Example 4;

[0041] Figure 5 The metallographic photograph of the electrolytic phosphating film obtained in Comparative Example 5;

[0042] Figure 6 The metallographic photograph of the electrolytic phosphating film obtained in Comparative Example 6;

[0043] Figure 7 This is the result of EDS analysis of the electrolytic phosphating film obtained in Example 3;

[0044] Figure 8 This is the result of EDS analysis of the electrolytic phosphating film obtained in Comparative Example 4;

[0045] Figure 9 The results of the drawing test of the wires with phosphate films formed on the surfaces prepared in Examples 1-5 and Comparative Examples 1-5 are shown. DETAILED DESCRIPTION

[0046] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not intended to limit this application.

[0047] In this application, the term "and / or" describes the relationship between associated objects, indicating that three possible relationships exist. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0048] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0049] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0050] The terms used in the embodiments of the present application are for the purpose of describing specific embodiments only and are not intended to limit the present application. The singular forms "a", "an", "the" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms unless the context clearly indicates otherwise.

[0051] The weights of the relevant components mentioned in the examples of this application may not only refer to the specific content of each component, but also represent the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the examples of this application, it is within the scope disclosed in the examples of this application. Specifically, the mass described in the examples of this application may be a mass unit known in the chemical industry, such as μg, mg, g, kg, etc.

[0052] The terms "first" and "second" are used solely for descriptive purposes to distinguish objects, such as substances, from one another and should not be understood to indicate or imply relative importance or to implicitly specify the quantity of the technical features being referred to. For example, without departing from the scope of the embodiments of this application, a first XX may also be referred to as a second XX, and similarly, a second XX may also be referred to as a first XX. Thus, features defined as "first" or "second" may explicitly or implicitly include one or more of such features.

[0053] In the first aspect of the present application, a graphite electrode is provided, which is used in an electrolytic phosphating process. The microparticles released from the surface of the graphite electrode are evenly dispersed in the electrolyte and eventually adsorbed on the phosphating film layer of the metal wire, significantly improving the lubrication performance of the film layer.

[0054] The graphite plate comprises the following raw materials in percentage by weight: 10-20% of a binder, 1-5% of a conductive agent, 5-10% of carbon fiber, and the remainder being graphite powder.

[0055] In some embodiments, the graphite powder has a particle size of 32-100 μm. The binder comprises one or more of phenolic resin, epoxy resin, furan resin, or polytetrafluoroethylene resin. The conductive agent comprises one or more of graphene, carbon black, or carbon nanotubes. The carbon fiber comprises one or both of polyacrylonitrile-based carbon fiber and pitch-based carbon fiber.

[0056] In the present application, graphite powder serves as the main component of the electrode plate, providing good electrical conductivity and chemical stability. As released microparticles, after being adsorbed on the phosphating film layer, they can significantly improve the lubrication performance of the film layer.

[0057] In the present application, the binder is used as an additive to the electrode plate to fix the graphite powder on the electrode. The acid-resistant binder can withstand the acidic electrolytic phosphating solution and maintain the structural stability of the electrode.

[0058] In the present application, the conductive agent, as a part of the conductive network of the electrode plate, can effectively improve the conductivity of the electrode plate, reduce the internal resistance of the electrode plate, and reduce the power consumption of the electrolytic phosphating process.

[0059] In this application, carbon fiber can enhance the mechanical strength and flexibility of the plate, enabling it to withstand the mechanical stress that may be encountered during manufacturing and use, making the plate more durable during the electrolytic phosphating process.

[0060] The second aspect of the present application provides a method for preparing a graphite electrode. The prepared graphite electrode is used in an electrolytic phosphating process. The surface of the graphite electrode can release graphite particles, which are evenly dispersed in the electrolyte and eventually adsorbed on the phosphating film layer of the metal wire, significantly improving the lubrication performance of the film layer.

[0061] The preparation method of the graphite plate comprises:

[0062] S101. Add graphite powder and binder according to the formula ratio, heat, stir and mix them evenly to form a mixture.

[0063] S102. Add the conductive agent and carbon fiber to the mixture, continue heating and stirring to ensure that all ingredients are fully mixed to obtain a mixed raw material.

[0064] S103. Put the mixed raw materials into a mold and perform compression molding to obtain a molded blank.

[0065] S104. Take the formed blank out of the mold and perform a curing treatment to fully cure the adhesive.

[0066] S105. Slowly cool to room temperature to obtain a plate blank.

[0067] S106. Perform sandblasting on the plate blank to improve its surface roughness and increase the amount of released microparticles.

[0068] In some embodiments, the heating temperature in step S101 is 50° C.-140° C., and the stirring speed is maintained at 100-200 r / min.

[0069] In step S102, the heating temperature is 50° C.-80° C., and the stirring speed is maintained at 200-300 r / min.

[0070] In step S103 , the pressing temperature is 150-200° C., the injection pressure is 10-20 MPa, and the pressure is maintained for 2-6 minutes.

[0071] In the curing treatment of step S104, the heating temperature is 50° C.-140° C. and maintained for 12-24 hours.

[0072] In step S105, the mixture is cooled to room temperature at a cooling rate of 0.2-0.8°C / min.

[0073] In some embodiments, in the sandblasting surface treatment in step S106 , the abrasive is aluminum oxide, the abrasive particle size is 120-180 mesh, the sandblasting pressure is 0.4-0.6 MPa, and the sandblasting time is 10-15 minutes.

[0074] In this application, graphite powder and binder are added according to the formula ratio, heated, stirred and mixed to form a mixture. The purpose of this step is to ensure that the graphite powder and binder are fully mixed, providing a uniform raw material base for the subsequent preparation process.

[0075] In this application, the conductive agent and carbon fiber are added to the mixture, and the mixture is heated and stirred to ensure that all ingredients are fully mixed to obtain a mixed raw material. The purpose of this step is to evenly distribute the conductive agent and carbon fiber in the mixture of graphite powder and binder, thereby improving the conductivity and mechanical strength of the plate.

[0076] In this application, the mixed raw materials are placed in a mold and pressed to obtain a shaped blank. The purpose of this step is to form the raw materials into a blank with a certain shape and density through pressing, providing a semi-finished product with a stable shape for the curing process.

[0077] In this application, the formed blank is removed from the mold and subjected to a curing process to fully cure the binder. This step is to cure the binder, improve the mechanical strength and acid resistance of the plate, and ensure stable operation of the plate during the electrolytic phosphating process.

[0078] In this application, the plate blank is slowly cooled to room temperature to obtain the plate blank. This step is to prevent the plate blank from generating internal stress due to rapid temperature changes, which affects the structural integrity and service life of the plate.

[0079] In this application, the plate blank is sandblasted to improve its surface roughness and increase the release of microparticles. This step is used to form small grooves on the plate surface that are easy to release microparticles, thereby improving the release amount and uniformity of microparticles during the electrolytic phosphating process.

[0080] The third aspect of the present application provides a formula for an electrolytic phosphating solution for use with the above-mentioned graphite electrode. During the electrolytic phosphating process, the microparticles released from the surface of the graphite electrode are evenly dispersed in the electrolytic phosphating solution and ultimately adsorbed on the phosphating film layer of the metal wire, significantly improving the lubrication performance of the film layer.

[0081] Each liter of electrolytic phosphating solution includes the following raw materials:

[0082] Phosphoric acid 130-150g, zinc oxide 75-90g, nitrate 80-120g, succinic acid 3-5g, citric acid 3-5g, polyphosphate 3-5g, polycarboxylate 3-5g, dodecylphenol polyoxyethylene ether 0.3-0.5g.

[0083] In some embodiments, the nitrate is any one or more of calcium nitrate, manganese nitrate, and nickel nitrate.

[0084] In some embodiments, the polyphosphate is any one or more of tripolyphosphate (CAS#: 7758-29-4, 13845-36-8, or 14728-39-3) and tetrapolyphosphate (CAS#: 14986-84-6 or 7727-67-5).

[0085] In some embodiments, the polycarboxylate is any one or more of polyacrylic acid (CAS#: 9003-01-4 or 9007-20-9) or polyacrylate (CAS#: 25549-84-2, 25608-12-2 or 9003-03-6), polymethacrylic acid (CAS#: 25087-26-7) or polymethacrylate (CAS#: 25086-62-8), polyaspartic acid (CAS#: 25608-40-6) or polyaspartate (CAS#: 181828-06-8, 34345-47-6 or 31871-95-1).

[0086] In some embodiments, each liter of electrolytic phosphating solution includes the following raw materials:

[0087] Phosphoric acid 140 g, zinc oxide 80 g, nitrate 100 g, succinic acid 4 g, citric acid 4 g, polyphosphate 4 g, polycarboxylate 4 g, dodecylphenol polyoxyethylene ether (CAS#: 68585-34-2, 32612-48-9 or 9041-29-6) 0.4 g.

[0088] In this application, the purpose of nitrate is to enhance current efficiency, optimize dispersibility, maintain the stability of active ingredients and control the balance between hydrogen evolution reaction and zinc reduction reaction. Nitrate ions can promote the improvement of phosphating solution current efficiency, ensure that more electric current is used for the effective formation of film layer, and reduce the loss of ineffective current. In addition, nitrate ions can also enhance the dispersibility of phosphating solution, which is most important for forming a uniform film layer on a workpiece with complex shapes. At the same time, nitrate ions help maintain the dissolved state of metal ions and prevent active ingredients from precipitating in the non-cathode area.

[0089] In this application, the combination of succinic acid and citric acid effectively buffers the free acid in the phosphating solution, enabling precise control of the solution's acidity and ensuring optimal electrochemical conditions during the electrolytic phosphating process. Acidity control is a key factor influencing film uniformity and quality. Adjusting this acid combination optimizes the coating's microstructure, reduces porosity and cracking, and ultimately improves the coating's appearance.

[0090] In the present application, polyphosphate and polycarboxylate are used as dispersants. These water-soluble polymer compounds can reduce the interaction force between graphite particles, prevent particle agglomeration, and promote particle dispersion.

[0091] In the present application, dodecylphenol polyoxyethylene ether is used as a dispersant surfactant to reduce the surface tension of the electrolytic phosphating solution and promote the dispersion and flow of graphite particles in the electrolyte.

[0092] The fourth aspect of the present application provides a method for preparing an electrolytic phosphating solution, which is used in conjunction with the above-mentioned graphite electrode. During the electrolytic phosphating process, the microparticles released from the surface of the graphite electrode are evenly dispersed in the electrolyte and eventually adsorbed on the phosphating film layer of the metal wire, significantly improving the lubrication performance of the film layer.

[0093] The preparation method of electrolytic phosphating comprises the following steps:

[0094] S201 according to the weight of the corresponding raw materials per liter of electrolytic phosphating solution, prepare the materials;

[0095] S202. Zinc oxide and phosphoric acid are added to deionized water, heated to 60-70°C, and stirred until the zinc oxide reaction is complete;

[0096] S203. Lower the temperature to 35-45 ° C, add nitrate, polyphosphate and polycarboxylate, and stir thoroughly until all the added raw materials are dissolved;

[0097] S204. Add succinic acid, citric acid, and dodecylphenol polyoxyethylene ether and stir until dissolved, then cool to room temperature to obtain an electrolytic phosphating solution.

[0098] In some embodiments, in step S202 , the temperature is maintained at 60° C.

[0099] In some embodiments, in step S203, the temperature is maintained at 45°C.

[0100] In some embodiments, in step S202, the stirring speed is maintained at 100-200 r / min.

[0101] In some embodiments, in step S203, the stirring speed is maintained at 80-160 r / min.

[0102] The fifth aspect of the present application provides an electrolytic phosphating process that utilizes graphite plates to release particles to enhance the lubrication performance of the electrolytic phosphating film layer. The above-mentioned graphite plates are used as the anode of the electrolytic phosphating process. During the electrolytic phosphating process, the particles that can be released from the surface of the graphite plates are evenly dispersed in the electrolyte and eventually adsorbed on the phosphating film layer of the metal wire, significantly improving the lubrication performance of the film layer.

[0103] The electrolytic phosphating process comprises the following steps:

[0104] S301. Install the graphite plate in the electrolytic phosphating tank as an anode and connect it to the positive electrode of the electrolytic power supply.

[0105] S302. Pour the electrolytic phosphating solution into the electrolytic phosphating tank, heat and stir.

[0106] S303. Connect the raw material coil wire to the straightening machine, sanding machine, conductive pressure wheel, water washing tank, electrolytic phosphating tank, post-water washing tank, and inverted wire taking-up machine in sequence.

[0107] S304. Set the current density and wire speed, turn on the electrolytic phosphating power supply and inverted wire take-up, and perform electrolytic phosphating treatment on the raw wire.

[0108] S305. A phosphating film is formed on the surface of the metal wire. At the same time, the microparticles released by the graphite plate enter the electrolyte and are adsorbed on the phosphating film, thereby enhancing the lubrication properties of the film.

[0109] In some embodiments, the heating temperature in step S302 is 40° C.-60° C., and the stirring speed is maintained at 100-200 r / min.

[0110] In some embodiments, the current density in step S304 is 5-25A / dm 2 , the routing speed is maintained at 0.61.6m / s.

[0111] In the present application, the electrolytic phosphating solution is heated and stirred. This step is used to promote the release of graphite particles into the electrolytic phosphating solution and accelerate the uniform distribution of the particles through heating and stirring.

[0112] In this application, the raw coiled wire is sequentially connected to a straightener, a sanding machine, a conductive pressure wheel, a water washing tank, an electrolytic phosphating tank, a post-water washing tank, and an inverted wire take-up machine. The purpose of this step is to ensure that the surface of the wire is clean and free of impurities through pretreatment steps (straightening, removing the oxide layer, water washing, etc.), to prepare for electrolytic phosphating and improve the adhesion and uniformity of the phosphating film.

[0113] In this application, the current density and wire speed are set, the electrolytic phosphating power supply is turned on, and the wire is inverted and taken up. The purpose of this step is to control the parameters of the electrolytic phosphating process, ensure the speed and quality of the phosphate film on the wire surface, and maintain production efficiency.

[0114] The following describes the details in conjunction with specific embodiments.

[0115] The raw materials used in the following examples can be purchased from the market, or can be obtained by self-preparation. As an example, the information on the ways to obtain raw materials in the specific implementation of the present invention is shown in the following table:

[0116] Raw material name CAS number Phenolic resin 26678-93-3 epoxy resin 24969-06-0 Furan resin 25212-86-6 polytetrafluoroethylene resin 25067-11-2 Polyacrylonitrile-based carbon fiber 70892-43-2 Pitch-based carbon fiber 8052-42-4

[0117] Example 1

[0118] A graphite plate comprises the following raw materials by weight:

[0119] Phenolic resin 10%, epoxy resin 10%, graphene 3%, carbon black 2%, polyacrylonitrile-based carbon fiber 10%, and the balance is 100μm particle size graphite powder.

[0120] The method for preparing the graphite plate comprises the following steps:

[0121] S101. Add graphite powder and binder according to the formula ratio, heat to 140°C, and stir and mix at a speed of 200 r / min to form a mixture.

[0122] S102. Add the conductive agent and carbon fiber to the mixture, continue heating at 80°C, and stir and mix at a speed of 300 r / min to ensure that all ingredients are fully mixed to obtain a mixed raw material.

[0123] S103. Place the mixed raw materials into a mold and perform compression molding at a pressing temperature of 200°C and an injection pressure of 20 MPa. Maintain the pressure for 6 minutes to obtain a molded blank.

[0124] S104. The formed blank is removed from the mold and subjected to a curing treatment at a curing temperature of 140° C. for 24 hours to allow the adhesive to fully cure.

[0125] S105. Slowly cool to room temperature at a cooling rate of 0.8°C / min to obtain a plate blank.

[0126] S106. The electrode blank is subjected to sandblasting surface treatment, with aluminum oxide as the abrasive, a 180-mesh abrasive particle size, a sandblasting pressure of 0.6 MPa, and a sandblasting time of 15 minutes.

[0127] An electrolytic phosphating solution, each liter of which includes the following raw materials:

[0128] Phosphoric acid 150g, zinc oxide 90g, calcium nitrate 110g, nickel nitrate 10g, succinic acid 5g, citric acid 5g, sodium tripolyphosphate 5g, sodium polyacrylate 5g, dodecylphenol polyoxyethylene ether 0.5g, and the balance is water.

[0129] The preparation method of the electrolytic phosphating solution comprises the following steps:

[0130] S201 according to the weight of the corresponding raw materials per liter of electrolytic phosphating solution, prepare the materials;

[0131] S202. Zinc oxide and phosphoric acid were added to deionized water, heated to 70°C, stirred thoroughly, and the stirring speed was maintained at 200 r / min until the zinc oxide reaction was complete;

[0132] S203. Lower the temperature to 45 ° C, add nitrate (calcium nitrate, nickel nitrate), polyphosphate (sodium tripolyphosphate) and polycarboxylate (sodium polyacrylate), stir thoroughly, and maintain the stirring speed at 160r / min until all the added raw materials are dissolved;

[0133] S204. Add succinic acid, citric acid, and dodecylphenol polyoxyethylene ether and stir until dissolved, then cool to room temperature to obtain an electrolytic phosphating solution.

[0134] An electrolytic phosphating process that utilizes particles released from a graphite anode plate to enhance the lubrication performance of an electrolytic phosphating film layer comprises the following steps:

[0135] S301. Install the graphite plate in the electrolytic phosphating tank as an anode and connect it to the positive electrode of the electrolytic power supply.

[0136] S302. Pour the electrolytic phosphating solution into the electrolytic phosphating tank, heat and stir. The heating temperature is 60°C and the stirring speed is maintained at 200 r / min.

[0137] S303. Connect the raw material coil wire to the straightening machine, sanding machine, conductive pressure wheel, water washing tank, electrolytic phosphating tank, post-water washing tank, and inverted wire taking-up machine in sequence.

[0138] S304. Set the current density and wire speed, turn on the electrolytic phosphating power supply and inverted wire take-up, and perform electrolytic phosphating treatment on the raw wire. The current density is 25A / dm 2 , the routing speed is maintained at 1.6m / s.

[0139] S305. A phosphating film is formed on the surface of the metal wire. At the same time, the microparticles released by the graphite anode plate enter the electrolyte and are adsorbed on the phosphating film.

[0140] Example 2

[0141] A graphite plate comprises the following raw materials by weight:

[0142] 5% phenolic resin, 5% epoxy resin, 0.6% graphene, 0.4% carbon black, 5% polyacrylonitrile-based carbon fiber, and the balance is 32μm particle size graphite powder.

[0143] The method for preparing the graphite plate comprises the following steps:

[0144] S101. Add graphite powder and binder according to the formula ratio, heat to 50°C, and stir and mix at a speed of 100 r / min to form a mixture.

[0145] S102. Add the conductive agent and carbon fiber to the mixture, continue heating at 50°C, and stir and mix at a speed of 200 r / min to ensure that all ingredients are fully mixed to obtain a mixed raw material.

[0146] S103. Place the mixed raw materials into a mold and perform pressing molding at a pressing temperature of 150°C and an injection pressure of 10 MPa. Maintain the pressure for 2 minutes to obtain a molded blank.

[0147] S104. Remove the formed blank from the mold and perform a curing treatment at a curing temperature of 50°C for 12 hours to allow the adhesive to fully cure.

[0148] S105. Slowly cool to room temperature at a cooling rate of 0.2°C / min to obtain a plate blank.

[0149] S106. Perform sandblasting on the electrode blank, using aluminum oxide as the abrasive, 120 mesh as the abrasive, 0.4 MPa as the sandblasting pressure, and 10 min as the sandblasting time.

[0150] An electrolytic phosphating solution, each liter of which includes the following raw materials:

[0151] Phosphoric acid 130g, zinc oxide 75g, calcium nitrate 75g, nickel nitrate 5g, succinic acid 3g, citric acid 3g, sodium tripolyphosphate 3g, sodium polyacrylate 3g, dodecylphenol polyoxyethylene ether 0.3g, and the balance is water.

[0152] The preparation method of the electrolytic phosphating solution comprises the following steps:

[0153] S201 according to the weight of the corresponding raw materials per liter of electrolytic phosphating solution, prepare the materials;

[0154] S202. Zinc oxide and phosphoric acid were added to deionized water, heated to 60°C, stirred thoroughly, and the stirring speed was maintained at 100 r / min until the zinc oxide reaction was complete;

[0155] S203. Lower the temperature to 45 ° C, add nitrate, polyphosphate and polycarboxylate, stir thoroughly, and maintain the stirring speed at 80r / min until all the added raw materials are dissolved;

[0156] S204. Add succinic acid, citric acid, and dodecylphenol polyoxyethylene ether and stir until dissolved, then cool to room temperature to obtain an electrolytic phosphating solution.

[0157] An electrolytic phosphating process that utilizes particles released from a graphite anode plate to enhance the lubrication performance of an electrolytic phosphating film layer comprises the following steps:

[0158] S301. Install the graphite plate in the electrolytic phosphating tank as an anode and connect it to the positive electrode of the electrolytic power supply.

[0159] S302. Pour the electrolytic phosphating solution into the electrolytic phosphating tank, heat and stir. The heating temperature is 60°C and the stirring speed is maintained at 200 r / min.

[0160] S303. Connect the raw material coil wire to the straightening machine, sanding machine, conductive pressure wheel, water washing tank, electrolytic phosphating tank, post-water washing tank, and inverted wire taking-up machine in sequence.

[0161] S304. Set the current density and wire speed, turn on the electrolytic phosphating power supply and inverted wire take-up, and perform electrolytic phosphating treatment on the raw wire. The current density is 25A / dm 2 , the routing speed is maintained at 1.6m / s.

[0162] S305. A phosphating film is formed on the surface of the metal wire. At the same time, the microparticles released by the graphite anode plate enter the electrolyte and are adsorbed on the phosphating film.

[0163] Example 3

[0164] A graphite plate comprises the following raw materials by weight:

[0165] Phenolic resin 7.5%, epoxy resin 7.5%, graphene 2%, carbon black 1%, polyacrylonitrile-based carbon fiber 7.5%, and the balance is 66μm particle size graphite powder.

[0166] The method for preparing the graphite plate comprises the following steps:

[0167] S101. Add graphite powder and binder according to the formula ratio, heat to 95°C, and stir and mix at a speed of 150 r / min to form a mixture.

[0168] S102. Add the conductive agent and carbon fiber to the mixture, continue heating to 65°C, and stir and mix at a speed of 250 r / min to ensure that all ingredients are fully mixed to obtain a mixed raw material.

[0169] S103. Place the mixed raw materials into a mold and perform compression molding at a pressing temperature of 175°C and an injection pressure of 15 MPa. Maintain the pressure for 4 minutes to obtain a molded blank.

[0170] S104. The formed blank is removed from the mold and subjected to a curing treatment at a curing temperature of 95° C. for 18 hours to allow the adhesive to fully cure.

[0171] S105. Slowly cool to room temperature at a cooling rate of 0.5°C / min to obtain a plate blank.

[0172] S106. The electrode blank is subjected to sandblasting surface treatment, with aluminum oxide as the abrasive, a 150-mesh abrasive particle size, a sandblasting pressure of 0.5 MPa, and a sandblasting time of 12.5 min.

[0173] An electrolytic phosphating solution, each liter of which includes the following raw materials:

[0174] Phosphoric acid 140g, zinc oxide 82.5g, calcium nitrate 92.5g, manganese nitrate 5g, nickel nitrate 2.5g, succinic acid 4g, citric acid 4g, potassium tripolyphosphate 4g, sodium polyacrylate 4g, dodecylphenol polyoxyethylene ether 0.4g, and the balance is water.

[0175] The preparation method of the electrolytic phosphating solution comprises the following steps:

[0176] S201 according to the weight of the corresponding raw materials per liter of electrolytic phosphating solution, prepare the materials;

[0177] S202. Zinc oxide and phosphoric acid were added to deionized water, heated to 65°C, stirred thoroughly, and the stirring speed was maintained at 150 r / min until the zinc oxide reaction was complete;

[0178] S203. Lower the temperature to 40 ° C, add nitrate, polyphosphate and polycarboxylate, stir thoroughly, and maintain the stirring speed at 120r / min until all the added raw materials are dissolved;

[0179] S204. Add succinic acid, citric acid, and dodecylphenol polyoxyethylene ether and stir until dissolved, then cool to room temperature to obtain an electrolytic phosphating solution.

[0180] An electrolytic phosphating process that utilizes particles released from a graphite anode plate to enhance the lubrication performance of an electrolytic phosphating film layer comprises the following steps:

[0181] S301. Install the graphite plate in the electrolytic phosphating tank as an anode and connect it to the positive electrode of the electrolytic power supply.

[0182] S302. Pour the electrolytic phosphating solution into the electrolytic phosphating tank, heat and stir. The heating temperature is 50°C and the stirring speed is maintained at 150 r / min.

[0183] S303. Connect the raw material coil wire to the straightening machine, sanding machine, conductive pressure wheel, water washing tank, electrolytic phosphating tank, post-water washing tank, and inverted wire taking-up machine in sequence.

[0184] S304. Set the current density and wire speed, turn on the electrolytic phosphating power supply and inverted wire take-up, and perform electrolytic phosphating treatment on the raw wire. The current density is 15A / dm 2 , the routing speed is maintained at 1.1m / s.

[0185] S305. A phosphating film is formed on the surface of the metal wire. At the same time, the microparticles released by the graphite anode plate enter the electrolyte and are adsorbed on the phosphating film.

[0186] Example 4

[0187] A graphite plate comprises the following raw materials by weight:

[0188] Phenolic resin 10%, epoxy resin 10%, graphene 3%, carbon black 2%, polyacrylonitrile-based carbon fiber 10%, and the balance is 100μm particle size graphite powder.

[0189] The method for preparing the graphite plate comprises the following steps:

[0190] S101. Add graphite powder and binder according to the formula ratio, heat to 140°C, and stir and mix at a speed of 200 r / min to form a mixture.

[0191] S102. Add the conductive agent and carbon fiber to the mixture, continue heating at 80°C, and stir and mix at a speed of 300 r / min to ensure that all ingredients are fully mixed to obtain a mixed raw material.

[0192] S103. Place the mixed raw materials into a mold and perform compression molding at a pressing temperature of 200°C and an injection pressure of 20 MPa. Maintain the pressure for 6 minutes to obtain a molded blank.

[0193] S104. The formed blank is removed from the mold and subjected to a curing treatment at a curing temperature of 140° C. for 24 hours to allow the adhesive to fully cure.

[0194] S105. Slowly cool to room temperature at a cooling rate of 0.8°C / min to obtain a plate blank.

[0195] S106. The electrode blank is subjected to sandblasting surface treatment, with aluminum oxide as the abrasive, a 180-mesh abrasive particle size, a sandblasting pressure of 0.6 MPa, and a sandblasting time of 15 minutes.

[0196] An electrolytic phosphating solution, each liter of which includes the following raw materials:

[0197] Phosphoric acid 130g, zinc oxide 75g, calcium nitrate 75g, nickel nitrate 5g, succinic acid 3g, citric acid 3g, sodium tripolyphosphate 3g, sodium polyacrylate 3g, dodecylphenol polyoxyethylene ether 0.3g, and the balance is water.

[0198] The preparation method of the electrolytic phosphating solution comprises the following steps:

[0199] S201 according to the weight of the corresponding raw materials per liter of electrolytic phosphating solution, prepare the materials;

[0200] S202. Zinc oxide and phosphoric acid were added to deionized water, heated to 60°C, stirred thoroughly, and the stirring speed was maintained at 100 r / min until the zinc oxide reaction was complete;

[0201] S203. Lower the temperature to 45 ° C, add nitrate, polyphosphate and polycarboxylate, stir thoroughly, and maintain the stirring speed at 80r / min until all the added raw materials are dissolved;

[0202] S204. Add succinic acid, citric acid, and dodecylphenol polyoxyethylene ether and stir until dissolved, then cool to room temperature to obtain an electrolytic phosphating solution.

[0203] An electrolytic phosphating process that utilizes particles released from a graphite anode plate to enhance the lubrication performance of an electrolytic phosphating film layer comprises the following steps:

[0204] S301. Install the graphite plate in the electrolytic phosphating tank as an anode and connect it to the positive electrode of the electrolytic power supply.

[0205] S302. Pour the electrolytic phosphating solution into the electrolytic phosphating tank, heat and stir. The heating temperature is 60°C and the stirring speed is maintained at 200 r / min.

[0206] S303. Connect the raw material coil wire to the straightening machine, sanding machine, conductive pressure wheel, water washing tank, electrolytic phosphating tank, post-water washing tank, and inverted wire taking-up machine in sequence.

[0207] S304. Set the current density and wire speed, turn on the electrolytic phosphating power supply and inverted wire take-up, and perform electrolytic phosphating treatment on the raw wire. The current density is 25A / dm 2, the routing speed is maintained at 1.6m / s.

[0208] S305. A phosphating film is formed on the surface of the metal wire. At the same time, the microparticles released by the graphite anode plate enter the electrolyte and are adsorbed on the phosphating film.

[0209] Example 5

[0210] A graphite plate comprises the following raw materials by weight:

[0211] 5% phenolic resin, 5% epoxy resin, 0.6% graphene, 0.4% carbon black, 5% polyacrylonitrile-based carbon fiber, and the balance is 32μm particle size graphite powder.

[0212] The method for preparing the graphite plate comprises the following steps:

[0213] S101. Add graphite powder and binder according to the formula ratio, heat to 50°C, and stir and mix at a speed of 100 r / min to form a mixture.

[0214] S102. Add the conductive agent and carbon fiber to the mixture, continue heating at 50°C, and stir and mix at a speed of 200 r / min to ensure that all ingredients are fully mixed to obtain a mixed raw material.

[0215] S103. Place the mixed raw materials into a mold and perform pressing molding at a pressing temperature of 150°C and an injection pressure of 10 MPa. Maintain the pressure for 2 minutes to obtain a molded blank.

[0216] S104. Remove the formed blank from the mold and perform a curing treatment at a curing temperature of 50°C for 12 hours to allow the adhesive to fully cure.

[0217] S105. Slowly cool to room temperature at a cooling rate of 0.2°C / min to obtain a plate blank.

[0218] S106. Perform sandblasting on the electrode blank, using aluminum oxide as the abrasive, 120 mesh as the abrasive, 0.4 MPa as the sandblasting pressure, and 10 min as the sandblasting time.

[0219] An electrolytic phosphating solution, each liter of which includes the following raw materials:

[0220] Phosphoric acid 150g, zinc oxide 90g, calcium nitrate 110g, nickel nitrate 10g, succinic acid 5g, citric acid 5g, sodium tripolyphosphate 5g, sodium polyacrylate 5g, dodecylphenol polyoxyethylene ether 0.5g, and the balance is water.

[0221] The preparation method of the electrolytic phosphating solution comprises the following steps:

[0222] S201 according to the weight of the corresponding raw materials per liter of electrolytic phosphating solution, prepare the materials;

[0223] S202. Zinc oxide and phosphoric acid were added to deionized water, heated to 70°C, stirred thoroughly, and the stirring speed was maintained at 200 r / min until the zinc oxide reaction was complete;

[0224] S203. Lower the temperature to 45 ° C, add nitrate, polyphosphate and polycarboxylate, stir thoroughly, and maintain the stirring speed at 160r / min until all the added raw materials are dissolved;

[0225] S204. Add succinic acid, citric acid, and dodecylphenol polyoxyethylene ether and stir until dissolved, then cool to room temperature to obtain an electrolytic phosphating solution.

[0226] An electrolytic phosphating process that utilizes particles released from a graphite anode plate to enhance the lubrication performance of an electrolytic phosphating film layer comprises the following steps:

[0227] S301. Install the graphite plate in the electrolytic phosphating tank as an anode and connect it to the positive electrode of the electrolytic power supply.

[0228] S302. Pour the electrolytic phosphating solution into the electrolytic phosphating tank, heat and stir. The heating temperature is 60°C and the stirring speed is maintained at 200 r / min.

[0229] S303. Connect the raw material coil wire to the straightening machine, sanding machine, conductive pressure wheel, water washing tank, electrolytic phosphating tank, post-water washing tank, and inverted wire taking-up machine in sequence.

[0230] S304. Set the current density and wire speed, turn on the electrolytic phosphating power supply and inverted wire take-up, and perform electrolytic phosphating treatment on the raw wire. The current density is 25A / dm 2 , the routing speed is maintained at 1.6m / s.

[0231] S305. A phosphating film is formed on the surface of the metal wire. At the same time, the microparticles released by the graphite anode plate enter the electrolyte and are adsorbed on the phosphating film.

[0232] Comparative Example 1

[0233] An electrolytic phosphating process utilizing particles released from a graphite anode plate to enhance the lubrication performance of an electrolytic phosphating film layer comprises the following steps: adjusting the raw material composition of the graphite plate to 2.5% phenolic resin, 2.5% epoxy resin, 0% graphene, 0% carbon black, 2.5% polyacrylonitrile-based carbon fiber, and 92.5% graphite powder with a particle size of 66 μm, with the remaining conditions being the same as those in Example 3.

[0234] Comparative Example 2

[0235] An electrolytic phosphating process utilizing particles released from a graphite anode plate to enhance the lubrication performance of an electrolytic phosphating film layer comprises the following steps: the graphite plate is not subjected to the sandblasting treatment of step S106, and the remaining conditions are the same as those of Example 3.

[0236] Comparative Example 3

[0237] An electrolytic phosphating process does not prepare the above-mentioned graphite anode plate, does not use the above-mentioned graphite anode plate as an anode for electrolytic phosphating, but uses a ruthenium-iridium coated electrode plate for electrolytic phosphating, and the other conditions are the same as those in Example 3.

[0238] Comparative Example 4

[0239] An electrolytic phosphating process utilizing a graphite anode plate to release particles to enhance the lubrication performance of an electrolytic phosphating film layer comprises the following steps: polyphosphate, polycarboxylate, and dodecylphenol polyoxyethylene ether are not added to the electrolytic phosphating solution formula, and the remaining conditions are consistent with those of Example 3.

[0240] Comparative Example 5

[0241] An electrolytic phosphating process for enhancing the lubrication performance of an electrolytic phosphating film layer by releasing particles from a graphite anode plate comprises the following steps: Step S304 wherein the current density is 1A / dm 2 , the other conditions are the same as those in Example 3.

[0242] Comparative Example 6

[0243] An electrolytic phosphating process for enhancing the lubrication performance of an electrolytic phosphating film layer by releasing particles from a graphite anode plate comprises the following steps: Step S304 wherein the current density is 50A / dm 2 , the other conditions are the same as those in Example 3.

[0244] The technical indicators and test results of the graphite plates, electrolytic phosphating solutions, and wire rod phosphating films obtained in the above examples and comparative examples are summarized as follows:

[0245] The graphite plates prepared in Examples 1-5 and Comparative Examples 1 and 2 were tested. The bending strength of the graphite plates was tested according to GB / T 13465.2-2014, the compressive strength of the graphite plates was tested according to GB / T 13465.3-2014, and the resistance of the graphite plates was tested according to GB / T 24525-2009. The results are as follows: Figure 1 shown.

[0246] from Figure 1The results show that compared with the comparative example, the graphite plate in the embodiment has better bending strength, compressive strength and lower resistivity, indicating that the addition of carbon fiber and conductive agent in the graphite plate formula and the sandblasting surface treatment make the graphite plate have better mechanical strength and conductive properties, thereby improving its stability during the electrolytic phosphating process.

[0247] like Figure 2 As shown, the electrolytic phosphating solutions prepared in Example 3 and Comparative Examples 1, 2, and 3 were observed after use. The electrolytic phosphating solution of Example 3 exhibited a light gray color after use, indicating the appropriate release of graphite particles. The uniform color of the solution indicates that the graphite particles were evenly dispersed in the solution during the electrolysis process, without precipitation or aggregation. This uniform dispersion helps the graphite particles form a uniform phosphating film on the metal surface, thereby improving lubrication performance.

[0248] The electrolytic phosphating solution of Comparative Example 1 turned dark gray after use, with uneven color distribution. Photos show graphite precipitates at the bottom of the solution. This may be due to improper graphite plate formulation design and an unreasonable ratio of binder and other additives, resulting in excessive release of graphite particles during the electrolysis process, exceeding the solution's stable dispersion capacity and causing precipitation.

[0249] The electrolytic phosphating solution of Comparative Example 2 was almost transparent after use, indicating that the amount of graphite particles released was extremely small. This may be because the graphite plate preparation process did not include sandblasting, which prevented the surface of the graphite plate from effectively releasing graphite particles into the solution.

[0250] The electrolytic phosphating solution of Comparative Example 3 is still transparent after use. The comparative example does not use a graphite plate, which clearly indicates that no graphite particles are released.

[0251] like Figure 3-8 As shown, the metallographic photographs of the electrolytic phosphating films prepared in Example 3 and Comparative Examples 4, 5 and 6 were observed, and the electrolytic phosphating films prepared in Example 3 and Comparative Example 4 were subjected to EDS analysis.

[0252] It can be observed that:

[0253] like Figure 3 and Figure 7 As shown, the phosphate coating of Example 3 exhibits high uniformity and integrity. Metallographic and EDS analysis reveal that the phosphate coating is tightly bonded to the graphite particles, forming a continuous, defect-free covering. This dense coating not only uniformly covers the entire surface of the wire but also successfully fills surface grooves and microscopic defects, providing a smooth and uniform surface that contributes to improved lubrication performance.

[0254] like Figure 4 and Figure 8 As shown, the phosphate coating of Comparative Example 4 exhibits significant differences. Metallographic and EDS analysis reveal that the coating is primarily composed of phosphates and, as a result, the electrolytic phosphating solution formulation in Comparative Example 4 results in a relatively small amount of graphite particles transferred to the phosphate coating. Consequently, the coating exhibits uneven coverage, with noticeable defects and gaps, failing to completely fill the grooves and defects on the wire surface. This results in a decrease in the coating's lubricity.

[0255] like Figure 5 As shown in the metallographic photograph of Comparative Example 5, there is almost no obvious film formed on the wire surface. This is because the current density is too low, resulting in insufficient electrolytic phosphating reaction, which seriously affects the formation of the film layer. It cannot provide sufficient coverage and protection, exposing the substrate surface and poor lubrication performance.

[0256] like Figure 6 As shown, the metallographic photograph of Comparative Example 6 reveals a different problem. Due to excessive current density, the phosphate film's grain growth rate is too rapid, resulting in holes in the film's high-stress areas. This incomplete film not only fails to effectively cover the substrate, but also significantly degrades lubrication performance due to the film's damage in high-stress areas.

[0257] The wires with phosphate coatings on the surfaces prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to a pulling test. The wires were 22A in diameter and Pull to The aperture is The tungsten steel mold is used to record the pulling force of the wire during the drawing process using the HT-LL-2000 tensile strength tester. The results are as follows: Figure 9 shown.

[0258] The results show that the wires in the examples generally require lower pullout forces than those in the comparative examples, indicating that the phosphate coatings in the examples exhibit superior lubricity. The design of the graphite plate, electrolytic phosphating solution, and electrolytic phosphating process conditions in the examples optimizes the microstructure of the phosphate coating, resulting in the inclusion of lubricity-enhancing graphite particles. These particles act as a lubricant during the drawing process, reducing friction between the metal and the die.

[0259] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application should be included in the scope of protection of the present application.

Claims

1. A graphite plate, characterized in that: The following raw materials are included by weight percentage: 10-20% binder, 1-5% conductive agent, 5-10% carbon fiber, and the balance is graphite powder; The particle size of the graphite powder is 32-100 μm; The binder includes one or more of phenolic resin, epoxy resin, furan resin or polytetrafluoroethylene resin; The conductive agent includes one or more of graphene, carbon black or carbon nanotubes; The carbon fiber includes one or both of polyacrylonitrile-based carbon fiber and pitch-based carbon fiber.

2. A graphite plate according to claim 1, characterized in that: The method for preparing a graphite plate comprises the following steps: S101. The graphite powder and the binder are fed in the proportion of the raw materials for the graphite plate, heated, stirred and mixed to form a mixture; S102. The conductive agent and carbon fiber are added to the mixture, and heating and stirring are continued to obtain a mixed raw material; S103. The mixed raw materials are placed in a mold and pressed to obtain a molded blank; S104. The formed blank is removed from the mold and cured; S105. After curing, slowly cool to room temperature to obtain a plate blank; S106. Performing sandblasting on the surface of the electrode plate blank to obtain a graphite electrode plate.

3. A graphite plate according to claim 2, characterized in that: In step S106, the sandblasting surface treatment is performed with aluminum oxide as the abrasive, a grain size of 120-180 mesh, a sandblasting pressure of 0.4-0.6 MPa, and a sandblasting time of 10-15 min.

4. A graphite plate according to any one of claims 1 to 3, characterized in that: When the graphite plate is electrolytically phosphated, graphite particles can be released from the surface of the graphite plate, and the graphite particles are evenly dispersed in the electrolyte.

5. Electrolytic phosphating process, characterized in that: The graphite plate according to any one of claims 1 to 4 is used as an anode for electrolytic phosphating.

6. The electrolytic phosphating process according to claim 5, characterized in that: The following steps are involved: S301. The graphite plate is installed in the electrolytic phosphating tank as an anode and connected to the positive electrode of the electrolytic power supply; S302. The electrolytic phosphating solution is injected into the electrolytic phosphating tank, heated and stirred; S303. The raw material round wire is sequentially connected to the straightening machine, the abrasive belt machine, the conductive voltage wheel, the washing tank, the electrolytic phosphating tank, the post-washing tank, and the inverted wire take-up machine; S304. Set the current density and wire speed, turn on the electrolytic phosphating power supply and inverted wire collection, and perform electrolytic phosphating treatment on the raw wire.

7. The electrolytic phosphating process according to claim 6, characterized in that: In step S302, the heating temperature is 40-60°C, and the stirring speed is maintained at 100-200 r / min.

8. The electrolytic phosphating process according to claim 6, characterized in that: In step S304, the current density is 5-25A / dm 2 , the routing speed is maintained at 0.6 1.6m / s.

9. The electrolytic phosphating process according to claim 6, characterized in that: Each liter of electrolytic phosphating solution includes the following raw materials: Phosphoric acid 130-150g, zinc oxide 75-90g, nitrate 80-120g, succinic acid 3-5g, citric acid 3-5g, polyphosphate 3-5g, polycarboxylate 3-5g, dodecylphenol polyoxyethylene ether 0.3-0.5g.

10. Application of electrolytic phosphating process, characterized in that: The electrolytic phosphating process according to any one of claims 6 to 9 is applied to the surface treatment of raw wire material.

Citation Information

Patent Citations

  • Graphite polar plate and preparation method thereof, alkaline electrolytic bath and water electrolysis hydrogen production equipment

    CN115490459A

  • Preparation method of graphite polar plate, graphite polar plate and alkaline electrolytic bath

    CN115786958A

  • Phosphating solution suitable for room-temperature ultrasonic electrolytic phosphating as well as preparation method and application of phosphating solution

    CN118497864A